REFORMULASI TERHADAP PENGATURAN UJARAN KEBENCIAN (HATE SPEECH) MELALUI MEDIA SOSIAL DI INDONESIA - suci jolanda; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The development of information and communication technology is now increasingly sophisticated with the emergence of various kinds of social media. Many users of social media abuse by spreading false news bringing down others and even spreading hate speech that can harm a group. The rise of hate speech (hate speech) is increasingly gaining attention from the public and law enforcement officials. Hate speech can encourage incitement, discrimination, violence, and even national divisions. The Electronic Information and Transaction Law (ITE Law) is a law that regulates hate speech on social media. In these laws the object of a criminal offense needs attention, because information intended to incite hatred is very biased in interpretationThis type of research can be classified into types of researchers Normative research or what is known as "legal research". This normative research uses the type of legal systematic research that can be carried out on certain laws or written laws. In legal research conducted by examining library materials or secondary data. The purpose of the group is to carry out identification of the basic orbasic notions in law.From the results of the research problem there are two main things that can be concluded. First, the definition of hate speech requires identification of elements of a criminal offense. Hate speech is all actions and direct or indirect attempts to incite a person or more spread hatred based on ethnicity, religion, race and between groups carried out on various social media. Secondly, in order to be able to explain specifically the meaning between groups because in principle the formulation of criminal law must be certain and strict so that it cannot be interpreted widely. The author's advice is the need for socialization or outreach to the community so that they can wisely use social media.Keywords: Hate Speech- Arrangement – Reformulation